PENGEMBANGAN E-COMIC BERBASIS AI “PETINJU” (PETUALANGAN TINO JUJUR) TENTANG MATERI PERILAKU TERPUJI PADA PEMBELAJARAN PAI KELAS 3 SD - Andini, Wanda Sri; Septiani, Putri; Sarti, Sarti; Aeni, Ani Nur (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This research aims to developan AI based e-comic for Pembelajaran Agama Islam (PAI) with a focus on commendable behavior material. Apart from that, this e-comic aims to convey a key message about the importance of honesty in everyday life. The research method used is the Design and Development (D&D) method with a development design using the ADDIE model which is designed to provide interatic and fun learning experiences for students by utilizing AI technology. After development, this e-comic was evaluated through field trials. The evaluation results show that e-comics can be effective in increasing students understanding of commendable behavior material in PAI. The implication of this research is to contribute to the development of technology-based learning media to support PAI learning that is more interactive and interesting.